Ontology modeling method applied in simulation modeling of distribution network time series operation - Luo, Fengzhang; Feng, Shaoting; Yang, Yang; Ao, Zhiqi; Li, Xueling; Chai, Yanxin (Frontiers in Energy Research, 2022)
Aiming at the difficulties in the realization of timing simulation in the digital twin environment, this paper proposes an ontology modeling method applied to the simulation modeling of distribution network timing series operation. Firstly, the two-layer ontology modeling architecture is introduced, and the power system domain structure ontology and the business-based application ontology are constructed. Secondly, based on the dynamic ontology modeling method, combined with the operational simulation business requirements, the sequential operation simulation ontology model is dynamically constructed. Finally, the effects of the modeling method in terms of simulation expression and modeling efficiency are shown through practical application example, and the modeling methods are compared and analyzed. The results provide a reference for the technical realization of power grid modeling under digital twin environments.